KERUSAKAN TEGAKAN TINGGAL DAN PRODUKTIVITAS KERJA PADA TEBANG PENJARANGAN SECARA SELEKTIF; KASUS DI SATU PERUSAHAAN HTI DI SUMATERA SELATAN - Sona Suhartana; Dulsalam Dulsalam (Pusat Penelitian dan Pengembangan Hasil Hutan, 2001)
The study was carried out at a timber estate company in South Sumatera in 1999. The aim of the study is to know the effect of selective thinning to residual stand damage and work productivity.Data collected were: thinned and damaged trees; residual stand; thinning time; diameter and length of thinned trees. The data was analyzed by tabulation.The results of the study showed that the average of residual stand damaged and the average of work productivity in selective thinning are respectively 6.22% and 56.167 m3/hour.Key words : Selective thinning, residual stand damaged, work productivity.